The Relationship of Parenting Patterns to Effective Communication in Pre-School Children - Delence Khaysia Salim; Heny Prasetyorini; Niken Sukesi (GLOBAL HEALTH SCIENCE GROUP, 2022)
Parenting is a determinant and influence on the child's personality, including the nature and behavior of children. Children become good or bad depending on the upbringing. This must be applied in order to realize a good parenting pattern, namely by exemplary, consistent, positive discipline without violence, habituation and effective communication. Effective communication is the initial ability to communicate and interact socially, as well as help children's language development, so parents and educators must provide opportunities for good speech. This study aims to determine the relationship between parenting styles and effective communication in preschool children at Mekarsari. The type of research used is quantitative with descriptive correlational research method. The research instrument used was a questionnaire in the form of a google form and this questionnaire was not tested for validity with a value of 0.912 and a reliability test of 0.956. Respondents in this study consisted of 43 parents at Mekarsari, desa Jenarsari, Kecamatan Gemuh, kabupaten Kendal, which were taken using a total sampling technique and using the Spearman Rank test. The results of the study showed a p value of 0.004 and Rho = 0.429 where Ho was rejected and Ha was accepted, meaning that there is a relationship between parenting styles and effective communication in pre-school children at Mekarsari.